Analisis Sistem Pembiayaan Karyawan dengan Akad Murabahah di BPRS Madinah Lamongan - Aisyatur Rohmah; Dwi Aprilianto (Universitas Islam Lamongan, 2023)
This research is motivated by the products offered by BPRS Madinah Lamongan, namely employee financing products with murabahah which recently has quite high demand from customers. Employee financing is provided to internal employees and general employees of BPRS Madinah Lamongan for consumptive purposes. This research is field research. Data sources consist of primary and secondary data using data collection methods of observation, interviews and documentation. After the data is collected, the writer analyzes the data using qualitative descriptive methods with descriptive, inductive and deductive methods. The findings reveal that the employee financing system with murabahah in BPRS Madinah Lamongan principally is in line with Islamic economics. Its impact and influence are very positive. Likewise with the implementation, elements of irregularities according to the Islamic economic system have yet to be discovered.